2010
DOI: 10.1097/aog.0b013e3181e79440
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Suppression in Normal-Weight and Obese Women During Oral Contraceptive Use

Abstract: : I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 24 publications
3
40
0
2
Order By: Relevance
“…Discordance in diaries and direct biological markers of compliance,44 and an association between ovulation and compliance, not obesity, confirmed by a biological marker of COC compliance (i.e. serum LNG level) further emphasize the importance of compliance measurements in future clinical trials 45. HC compliance data should be collected in clinical trials using methods other than selfreporting to improve accuracy and reduce biases.…”
mentioning
confidence: 94%
“…Discordance in diaries and direct biological markers of compliance,44 and an association between ovulation and compliance, not obesity, confirmed by a biological marker of COC compliance (i.e. serum LNG level) further emphasize the importance of compliance measurements in future clinical trials 45. HC compliance data should be collected in clinical trials using methods other than selfreporting to improve accuracy and reduce biases.…”
mentioning
confidence: 94%
“…No excessive weight gain has been observed [Gallo et al 2014] and no definite relation between weight and contraceptive efficacy has been established [Westhoff et al 2010]. Data have indicated a decreased resorption of COC after bariatric surgery [Paulen et al 2010] but so far, no studies of pharmacokinetics after bariatric surgery using modern surgical procedures have been performed.…”
Section: Prescriptions Under Special Circumstancesmentioning
confidence: 99%
“…It has been shown that self-report of compliance can be erroneous and misleading. Specifically, assessment of OC treatment compliance using LNG level (the OC progestin component) in blood specimens collected over time found that 17% of study subjects were noncompliant, defined as nonusers or inconsistent users, even though their diary self-report supported compliance, and these subjects showed high rates of ovulation [23]. Thus, any differences seen between treatment groups in ovarian activity in the current study are likely primarily due to inconsistent compliance with treatment regimens.…”
Section: Discussionmentioning
confidence: 51%